Proposal of projects for the Outreach Committee of the Foreign Language Department to be offered to students enrolled in the Major of Modern Languages to develop their community outreach - Rivas Ortiz, Jessica Del Carmen; Ramírez Avalos, Jocelyn Marina; Díaz Ríos, Willian José; Rodríguez Argueta, Francisco Antonio; Contreras Cárcamo, Mauricio Salvador (San Salvador, El Salvador : Universidad de El Salvador, 2020)
Studying a major at the university is one of the biggest objectives that people have in life, the process is long, it is not easy, but people make sacrifices in order to get it. Having a major is not just attending classes, it is necessary to give time to make research, to study for different activities, sometimes people must participate in extracurricular activities but all of that has as a result obtaining a title. When studentsare in the 3 rd or 4 th year of the bachelor, they are required with something very important that is the social service project. The social service project is a requirement that must be fulfilled at the time people want to graduate, the social service project is the way which students use to give back to the society what it has been done to them in the time of the major, the students are plenty of abilities that they acquired studying and the best way to practice what they have learned is the social service. Every university student is asked for the social service project, each student must give 100 hours back for every academic year cursed in the university, and commonly 500 hours are required. The Outreach Committee Unit is the one that registers every process also is the one who monitors that students really work on what they must. Every department of the University has a Sub-Unit in order to attend students. The Outreach Committee Sub-Unit, year by year tries to give to the students the best options of project so that students can check them, and they can choose one, the Department of Foreign Languages is formed by two majors: Bachelor in English Teaching and Bachelor in Modern Languages specialty French and English. Most of the time the projects proposed by the Outreach Committee Sub Unit has as a requirement to be a student of Bachelor and English Teaching, so the students from this major tend to have more options that the ones that are part of Bachelor in Modern Languages Specialty in French and English. Due to the lack of projects for Modern Languages Students the researchers decided to focus on the problematic, and the main objective that they proposed was to find places where students from Bachelor in Modern Languages specialty in French and English can carry out a social service project. The most important was to carry to the Outreach Committee sub-unit proposals that really help the students in this process.
Incluye anexos e Información de las fuentes.
Texto en inglés.
Keywords: Idiomas -Enseñanza; Servicio social-estudiantes